Tingkat Pencemaran Lindi Pada Air Tanah Dangkal Di Sekitar TPA Kebon Kongok Menggunakan Parameter Fisika dan Kimia - Amalia Syuzita; Lalu Ahmad Didik Meiliyadi; Bahtiar Bahtiar (Lambung Mangkurat University Press, 2022)
Research has been conducted on the level of pollution caused by Leachate in shallow groundwater around Kebon Kongok landfill, Gerung, West Lombok. This research was conducted considering that water has many benefits in daily life, so it is important to know the quality of the water consumed. The research used experimental methods by analyzing physical parameters (Temperature, conductivity, pH and TDS) and chemical parameters in the form of heavy metal content (Pb, Fe, Cu and Mn). The results of physical parameter tests mostly show that the quality of shallow groundwater is still within the safe quality standard, there is 1 shallow groundwater point that is polluted due to the close proximity to the leachate. Chemical parameters indicate that the content of heavy metals is mostly well below the quality standard, except Cu metal is detected at 0.029 mg / l and Mn metal 1,457 mg / l at a distance of 50 m.KEYWORDS : Leachate; Shallow Water; Physics Parameters; Chemical Parameters